2010
DOI: 10.1007/s11432-010-4119-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistic characteristic analysis of forward scattering surface clutter in bistatic radar

Abstract: In this paper, based on the processing results of measured forward scattering clutter data in bistatic radar, using the Gaussian distribution model, Exponential distribution model, Power-Law distribution model, high order Auto-Regressive model and so on, the probability density distribution and power spectrum mathematical model are obtained, and the impact of clutter statistic models on target detection performance is analytically derived from statistic theory. According to the estimated clutter probability di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Compared with the Doppler signal, the magnitude will not change much during the observation time, and it is largely determined by the propagation mechanism and target scattering model rather than the motion parameter of the target. More details about the characteristic of magnitude can be looked up in [17][18][19][20][21]. On the contrary, the Doppler signal changes much more rapidly with the moving of the target.…”
Section: Signal Model Of Ground Moving Target In Fsrmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the Doppler signal, the magnitude will not change much during the observation time, and it is largely determined by the propagation mechanism and target scattering model rather than the motion parameter of the target. More details about the characteristic of magnitude can be looked up in [17][18][19][20][21]. On the contrary, the Doppler signal changes much more rapidly with the moving of the target.…”
Section: Signal Model Of Ground Moving Target In Fsrmentioning
confidence: 99%
“…Moreover, foliage clutter can be approximated as a narrowband Gaussian process [17][18][19][20][21], and the statistic characteristics in FSMR have empirically been estimated via the experimental data [18][19][20], thus the optimal detection procedure against clutter background in FSMR includes a whitening filter. Hence, the assumption that the target is detected against AWGN is also true for clutter presence.…”
Section: Introductionmentioning
confidence: 99%
“…Its target tracking technology attracted more and more attention in recent years. An existing challenge of BFSR is parameter estimation of aerial [2][3][4][5][6][7][8][9] and ground [10][11][12][13][14][15][16][17] targets. This article focuses on parameter estimation of aerial target trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent publications have discussed FSR for automatic ground target classification [12][13][14][15][16][17][18][19][20]. Recent studies on FSR reported in the cited literature have only been carried out for a small number of scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, surface clutter in the case of FSR has been physically modeled and statistically studied [19,20]. The use of FSR together with a low-cost system for the detection of ground targets could have applications in civil, defense, safety and security systems, such as systems for situation awareness and remote monitoring.…”
Section: Introductionmentioning
confidence: 99%